Closed Loop: Integrated Water, Nutrient, and Energy Recovery Systems for Sustainable Dairy Production (Case: Dairy Farming) - Stephanus Benedictus Bera Liwun (Asosiasi Dosen Muda Indonesia, 2026)
The dairy industry is very important to the economy, but it has big problems with sustainability since it doesn't use resources well and doesn't handle waste well. Eco-Efficiency (13.1%) and Technical Efficiency (58.7%) are still very low in Serbia because of ongoing structural inefficiencies. In Indonesia, where 90% of dairy farms are operated by smallholders, an estimated 84% of manure is discharged untreated, contributing to greenhouse gas emissions and eutrophication. To solve these problems, we need to use Circular Economy ideas, such as closed-loop nutrient, energy, and water flows and integrated resource recovery. This review evaluates opportunities, sustainability gains, and barriers to implementing closed-loop systems across the dairy supply chain. The objectives include assessing farm-level efficiency, quantifying environmental and economic benefits of manure-derived resource recovery, evaluating circular feed substitution, and analysing biogas adoption barriers among smallholders. The research integrates findings from Stochastic Frontier Analysis, Life Cycle Assessment and Costing, Multi-regional Input–Output analysis, membrane-based water reuse models, and system dynamics, complemented by qualitative surveys of Indonesian farmers. Integrated recovery systems yielded carbon-negative results (up to –1790 kg CO₂ eq/year) and significant economic advantages (825–1,056/year). Biogas cut down on the consumption of LPG by about 45%. Circular feeds made more milk and had less of an effect, while treating whey membranes slashed the need for fresh water by 67–90%. Closed-loop solutions make dairy farming much more sustainable, but they need help from policymakers to be able to grow because of high investment costs and ongoing structural inefficiencies.